Everolimus‐eluting bioresorbable vascular scaffold implantation to treat saphenous vein graft disease, single‐center initial experience. (10th August 2017) - Picard, Fabien; Marquis‐Gravel, Guillaume; Avram, Robert; Ly, Hung Q.; Dorval, Jean‐François; Doucet, Serge; de Hemptinne, Quentin; L'allier, Philippe L.; Tanguay, Jean‐François
Abstract : Aims: Recent studies have shown favorable outcomes with everolimus‐eluting bioresorbable vascular scaffold (BVS) in patients with stable coronary artery disease. Data on the use of BVS in saphenous vein graft disease (SVG) is currently lacking. Methods and Results: A total of 10 consecutive patients (13 lesions, including 6 in‐stent restenosis) who underwent BVS for SVG disease between May 2013 and June 2015 at a tertiary care institution were included. Median follow‐up period was 874 (720‐926) days. One patient had scaffold thrombosis (ScT) 15 months after implantation, which was treated medically. Another patient had target lesion revascularization (TLR) in two different lesions, where BVS was used to treat in‐stent restenosis. The composite endpoint of TLR, ScT, target vessel myocardial infarction, and cardiac death, was reached in two patients Conclusions: This first real‐world data on the use of the ABSORB™ BVS in patients with SVG disease shows that its implantation is technically feasible. The observed rate of target lesion revascularization was similar to those observed with drug‐eluting stents in similar settings. Larger studies are required to better define the optimal use of BVS to treat SVG disease.